Peningkatan Pemahaman Konsep Mata Kuliah Analisis Vektor Melalui Penerapan Problem Based Learning (PBL) Mahasiswa Tadris Matematika UIN Raden Mas Said Surakarta - Ratna Herawati; Wiwin Astuti; Anita Purnamasari (Action Research Journal, 2024)
Education aims to improve the quality of human life which is technically done through lectures. Good lectures will produce students' ability to learn continuously through their environment. The lecture process is composed of components that are interconnected with each other. The role of lecturers in teaching is very important. The interaction between lecturers and students during lectures plays an important role in achieving goals. Vector Analysis is a subject that plays an important role in the Mathematics family. Many mathematics students think that the Vector Analysis course is difficult. Lecture success can be measured from the level of conceptual understanding of the lecture material. However, in reality, the conceptual understanding of the Vector Analysis course achieved by mathematics students is still low. Vector Analysis lectures at the Tadris Mathematics Study Program, Raden Mas Said Surakarta State Islamic University have not been able to increase students' understanding of the concepts of Vector Analysis. The factor that causes students' low understanding of concepts in learning Vector Analysis is lectures that are centered on lecturers. The aim of this research is to increase students' conceptual understanding of vector analysis courses through the application of Problem Based Learning (PBL). This research is a qualitative descriptive group with the type of Classroom Action Research. The data used are field notes and documentation. Based on the research results, it can be concluded that there is an increase in understanding of the concept of Vector Analysis through the application of Problem Based Learning (PBL).